Synthesis and Characterization of A Fascinating Coordination Polymer Metal-Organic Framework Featuring Cobalt (II) and 4,4'-Bipyridine - Kurniawan, Cepi (Universitas Jenderal Soedirman, 2024)
ABSTRACT. This investigation delineates the fabrication, comprehensive characterization, and electrochemical evaluation of a one-dimensional Cobalt-based Metal-Organic Framework (Co-MOFs), constructed from 4,4’-Bipyridine ligands and Cobalt (II) ions. The study aimed to perfect the synthesis protocol, elucidate the structural and compositional attributes of the resultant MOF, and probe its electrochemical performance. Utilizing the reflux method, renowned for its efficacy and eco-compatibility, we synthesized the MOF and affirmed its formation through a suite of analytical techniques, including Infrared (IR) spectroscopy, Ultraviolet-Visible (UV-Vis) spectroscopy, Atomic Absorption Spectroscopy (AAS), and electrical conductivity measurements. The synthesized Co-MOFs, chemically notated as [Co2(4,4'-bpy)2(SO4)(H2O)2]SO4·H2O, manifested as a one-dimensional coordination polymer. X-ray Diffraction (XRD) analysis unveiled its monoclinic crystallinity within the C2 space group. Electrochemical characterization uncovered a reversible redox system, evidenced by a robust peak current ratio (IPa/IPc = 7.5), indicative of efficient electron transfer processes. Furthermore, the Co-MOFs significantly augmented the kinetics of the oxygen evolution reaction (OER) in an alkaline aqueous solution, highlighting its potential as a superior catalyst in energy-related electrochemical applications. This work not only contributes to the field of MOF synthesis but also sets the stage for future explorations into their practical applications in sustainable energy systems. Keywords: Electrochemical properties, metal-organic framework, oxigen evolution reaction catalyst, 4,4’-bipyridine.